PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Agustina Mapadang (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to analyze the influence of corporate governance mechanisms on tax avoidance. Corporate governance mechanisms are measured by Independent Commissioners and Institutional Ownership while tax avoidance is measured by the Avoidance Tax Rate. The research population is all manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016 using purposive sampling method. The number of observations of 435 and the type of research is the analysis of causal relationships to see the effect of each variable. The results of the study show that corporate governance mechanisms negatively affect tax avoidance; the board of directors has a positive effect on tax avoidance and institutional ownership has a negative effect on the value of the company.